Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1038/s41598-018-38119-9
|View full text |Cite
|
Sign up to set email alerts
|

A method using electroporation for the protein delivery of Cre recombinase into cultured Arabidopsis cells with an intact cell wall

Abstract: Genome engineering in plants is highly dependent on the availability of effective molecular techniques. Despite vast quantities of research, genome engineering in plants is still limited in terms of gene delivery, which requires the use of infectious bacteria or harsh conditions owing to the difficulty delivering biomaterial into plant cells through the cell wall. Here, we describe a method that uses electroporation-mediated protein delivery into cultured Arabidopsis thaliana cells possessing an intact cell wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 40 publications
1
21
0
Order By: Relevance
“…Batch electroporation (EP) is an alternative method to directly deliver proteins into cultured mammalian cells (Lambert et al, 1990; Chakrabarti et al, 1989; Vienken et al, 1978; Shi et al, 2018; Furuhata et al, 2019). EP-mediated protein transduction has surged in recent years with applications ranging from, cellular structural biology and the delivery of isotopically labeled proteins for in-cell NMR measurements (Theillet et al, 2016) to the introduction of immunoglobulins for targeting and degradation of endogenous proteins (Clift et al, 2017), and the delivery of ribonucleotide particles (RNPs) for CRISPR-Cas9-mediated gene editing (Kim et al, 2014; Lin et al, 2014; Liang et al, 2015; Hashimoto and Takemoto, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Batch electroporation (EP) is an alternative method to directly deliver proteins into cultured mammalian cells (Lambert et al, 1990; Chakrabarti et al, 1989; Vienken et al, 1978; Shi et al, 2018; Furuhata et al, 2019). EP-mediated protein transduction has surged in recent years with applications ranging from, cellular structural biology and the delivery of isotopically labeled proteins for in-cell NMR measurements (Theillet et al, 2016) to the introduction of immunoglobulins for targeting and degradation of endogenous proteins (Clift et al, 2017), and the delivery of ribonucleotide particles (RNPs) for CRISPR-Cas9-mediated gene editing (Kim et al, 2014; Lin et al, 2014; Liang et al, 2015; Hashimoto and Takemoto, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The GUS gene encodes β-glucuronidase that catalyzes the hydrolysis of β-D-glucuronic acid residues from the non-reducing end of mucopolysaccharides. GUS-expressing cells and tissue can be visualized either by staining with a blue dye using X-Gluc or by the emitted fluorescence via utilization of the 6-chloro-4-methylumbelliferyl-β-D-glucuronide (CMUG) fluorogenic substrate [23,26]. Although these techniques enable the spatial visualization and quantification of gene expression, they are both invasive and time-consuming.…”
Section: Discussionmentioning
confidence: 99%
“…The A. thaliana T87 strain (RIKEN Bio Resource Center, Ibaraki, Japan) was maintained and transformed with Agrobacterium (Rhizobium radiobacter) according to a previously described protocol [23]. Briefly, the T87 cells were co-cultured with Agrobacterium cells carrying the binary plasmids for 2 d and selected by plating on hygromycin-containing agar.…”
Section: Cell Culture and Agrobacterium-mediated Transformation Of T8mentioning
confidence: 99%
“…Although plant and algae cells behave differently during their development, the reports showed that cell wall barriers can be penetrated as long as the electroporation conditions are optimized. In addition, Furuhata et al (2019) performed electroporation-mediated protein delivery into cultured Arabidopsis cells. The Cre recombinase was successfully transferred through the cell wall with high efficiency.…”
Section: Discussionmentioning
confidence: 99%